CALIBRATION, VALIDATION AND EVALUATION OF A LUMPED HYDROLOGIC MODEL IN A MOUNTAIN AREA IN SOUTHERN ECUADOR - Oñate Valdivieso, F. (2016)
The performance of the Temez lumped model is evaluated in six (6) basins located in the border region between Ecuador and Peru, in South America. The basin areas vary between 200 and 2642 km2. Precipitation and temperature recorded in 43 climatological stations in the study area were considered. For comparison, a semi-distributed model was also implemented. The model calibration and validation was performed with different portions of the observed data. The Temez model was able to reproduce acceptably flows during the dry season, showing marked differences in the rainy season. The performance of the Temez model decreased with an increase in catchment area. The limitations may be attributed to the low station density, to the quality of the information, and to the difficulty of representing with a lumped parameter, characteristics that have a wide spatial variation. The semi-distributed model showed better simulation capabilities; however, in small catchments the ability of both models is comparable. The study has shown that application of the Temez model in small catchments up to 300 km2 may be satisfactory.